Physical exercise in prevention and treatment of breast cancer lymphedema: a systematic review - Marques, Maria Beatriz (2023)
Introduction – The number of women who have survived breast cancer treatments has increased in the last years with the improvements in therapies and techniques. Therefore, it is necessary to increase the response to these women. Evidence suggests this treatment causes fatigue, pain, poor quality of life, less arm range of motion, and lymphedema. Evidence also indicates that physical exercise (PE) improves the quality of life of cancer survivors. Objective – To verify how and which physical exercise characteristics can prevent and treat breast cancer-related lymphedema. Methods – A systematic review was carried out using PubMed, PEDro, Web of Science, and Sport Discus as databases. Randomized controlled trials (RCT) were selected if written in English or Portuguese without a time limit and with ≥5 on PEDro scale. The population was women over 18 who submitted to breast cancer treatments. Results – Fourteen studies were selected, 2478 women. The analyzed evidence suggests that PE does not exacerbate breast cancer-related lymphedema and can even improve the composition of the arm (a reduction of the fat mass and an increase of the lean mass). It was possible to acknowledge to understand that physical exercise can prevent the incidence of lymphedema by 70%. It was demonstrated that PE (resistance training and aerobic exercise) is recommended for all women undergoing this type of treatment, even in the absence of lymphedema.